Endovascular Treatment of Very Small Intracranial Aneurysms: Meta-Analysis - Yamaki, V.N. (AJNR Am J Neuroradiol, 2016)
BACKGROUND AND PURPOSE: Outcomes of endovascular treatment of very small intracranial aneurysms are still not well-characterized. Recently, several series assessing coil embolization of tiny aneurysms have presented new promising results. Thus, we performed a systematic review and meta-analysis of studies evaluating endovascular treatment of very small intracranial aneurysms. MATERIALS AND METHODS: We conducted a computerized search of Scopus, Medline, and the Web of Science for studies on endovascular treatment of very small (≤3 mm in diameter) intracranial aneurysms published between January 1996 and May 2015. Using a random-effects model, we evaluated clinical and angiographic outcomes. RESULTS: Twenty-two studies with 1105 tiny aneurysms (844 ruptured and 261 unruptured) endovascularly treated were included. Postoperative and long-term complete occlusion was achieved in 85% (95% CI, 78%–90%) and 91% (95% CI, 87%–94%) of aneurysms, respectively. The recanalization rate was 6% (95% CI, 4%–11%) and retreatment occurred in 7% (95% CI, 5%–9%) of cases. Seventy-nine percent (95% CI, 64%–89%) of patients had good neurologic outcome at long-term follow-up. Intraprocedural rupture occurred in 7% (95% CI, 5%–9%) of the coiling procedures, while thromboembolic complications occurred in 4% (95% CI, 3%–6%). CONCLUSIONS: Coil embolization of very small intracranial aneurysms can be performed safely and effectively. In the case of unruptured aneurysms, procedure-related complications are not negligible. Patients and providers should consider such risks when engaged in a shared decision-making process.